English Wordplay Translation Into Indonesian In The Subtitle Of Friends Television Series - Fithri, Ayyuhatsanail; Suyudi, Ichwan (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2019)
In the new era of audiovisual translation (AVT), identifying the translation of wordplay from English into Indonesian in various English comedy movies and series is a massive task as the wordplay is a form of humor which quite problematic to translate. The fundamental issue in translating humor is about the diversity of languages and different linguistic typology. This paper is to investigate types of wordplay found in the subtitles of Friends and strategies applied to translate English wordplay into Indonesian. The data of this study was collected from a long American series entitled ‘Friends’ from season one to ten. Hence, the most appropriate method employed is qualitative. The sampling technique applied is purposive sampling. The total four types of wordplay found in an American series entitled ‘Friends’ to create laughter, namely: phonological and graphological structure (consists of homonymy, paronymy, and homophony), lexical structure (polysemy), morphological structure, and syntactic structure. In the translation strategies, there are three dominant ways used by the translator, namely: wordplay to wordplay, wordplay to non-wordplay, and editorial technique. However, most of the translator whom sub movies or series used wordplay to non-wordplay strategy. This technique has a significant effect in rendering the meaning to the target text that affects the audience when they watch the film whether to laugh or not to laugh. Pada era modern di mana bidang penerjemahan audio visual (AVT) berkembang, mengidentifikasi terjemahan wordplay (permainan kata) dari Bahasa Inggris ke Bahasa Indonesia dalam berbagai film dan serial komedi Barat merupakan tugas yang tidak mudah, mengingat permainan kata adalah salah satu bentuk humor yang cukup sulit diterjemahkan. Kendala dasar dalam menerjemahkan humor adalah mengenai keragaman bahasa dan tipologi linguistik yang berbeda. Tulisan ini membahas mengenai jenis wordplay dan strategi yang diterapkan untuk menerjemahkan wordplay dalam subtitle serial ‘Friends’. Data penelitian ini berasal dari serial Amerika berjudul 'Friends' dari season 1 hingga 10. Oleh karena itu, metode yang digunakan dalam tulisan ini adalah metode kualitatif. Teknik sampling yang digunakan dalam tulisan ini adalah teknik purposive sampling. Terdapat empat jenis permainan kata yang ditemukan dalam serial ‘Friends’, yaitu: struktur fonologis dan grafologis (terdiri dari homonimi, paronimi, dan homofoni), struktur leksikal (polisemi), struktur morfologis, dan struktur sintaksis. Sementara, dalam strategi penerjemahan, terdapat tiga cara yang paling dominan digunakan oleh penerjemah, yaitu: wordplay to wordplay, wordplay to non-wordplay, dan editorial technique. Namun, sebagian besar penerjemah subtitle dalam film atau serial komedi ini menggunakan strategi wordplay-nonwordplay. Teknik ini mempengaruhi efek kelucuan yang signifikan pada teks subtitle di bahasa target sehingga berpengaruh bagi penonton saat film atau serial ditonton.